(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The key characteristics of how to raise first-year university students’ reading performance comprise basic pedagogical knowledge and understanding, awareness of expressive classroom practices, and linguistic and communicative competence. Nurturing these traits amongst learners is a challenging issue, specifically when they have a prior lack of English language proficiency. One way of improving learners’ poor reading skills is the effective feedback given to them. This study investigates the efficiency of giving feedback to students to increase their reading abilities at the Foundation Institute in Taibah University. 15 EFL instructors who teach these students participated in the study. The descriptive method was applied and questionnaires were given to instructors to collect their views about the effects of feedback on students’ reading skills. The data was analysed via content analysis. The findings revealed that constructive feedback had made remarkable progress in students’ reading performance.